vocabulary acquisition through authentic english reading material on beginner young adult learners at the university - Vargas Bonilla, Jhonatan Alexander (2025)
The present study analyzes the use of authentic reading materials that assist in vocabulary acquisition; the main objective was to propose effective pedagogical strategies that improve vocabulary learning in beginner university students through real texts, such as blogs, articles, and news, which reflect the natural use of language in everyday contexts. The research responds to the need to overcome the limitations of traditional materials, which are often artificial and less motivating for students. It is theoretically grounded in approaches such as the comprehensible input hypothesis, self-determination theory, social learning, and constructivism, all of which highlight the importance of motivation, social interaction, contextualized exposure, and active participation in the learning process. The methodology used was mixed-focused, combining qualitative and quantitative data through surveys of students, interviews with teachers, classroom observations, and the application of a pre-test with the Vocabulary Knowledge Scale (VKS), where 32 first-semester students from the Language Pedagogy program at the Technical University of Quevedo were selected. The results show that students find authentic materials, such as blogs, useful for acquiring vocabulary in real contexts. However, many face frustration due to unfamiliar vocabulary, indicating a need to adapt these materials to their level. Additionally, strategies such as using synonyms, prior vocabulary lists, and guided activities were valued by students. It is concluded that authentic materials promote meaningful, motivating, and contextualized learning but require teacher guidance and adaptation to be effective. It is recommended to integrate them progressively, accompanied by collaborative activities, projects, and techniques that facilitate comprehension and practical use of the new vocabulary.